Individualizing Cancer Screening Recommendations: A Team-Based Learning Activity for Fourth-Year Medical Students - Paul A. Bergl; Jennifer Feagles (Association of American Medical Colleges, 2017)
Introduction Cancer screenings are key preventive services that patients receive in primary care. Health care professional students are generally taught about major society guidelines and U.S. Preventive Services Task Force recommendations for cancer screenings. Unfortunately, students and novice providers may view these influential recommendations as a rule book by which to provide care. Experienced providers recognize that not every patient fits neatly into clinical guidelines. Appropriate use of cancer screening entails an understanding of patient preferences, patient-specific health factors, and screening risks and associated pitfalls. Methods This 2-hour team-based learning (TBL) session immerses learners in three challenging patient scenarios that are designed to stimulate nuanced discussion of cancer screening using controversial cases. The scenarios encompass the following cases: (1) a 68-year-old man actively seeking prostate cancer screening, (2) a heavy smoker with psychiatric illness and alcoholism being considered for lung cancer screening, and (3) a 42-year-old woman seeking to become pregnant who inquires about breast cancer screening. Results The materials were originally designed for fourth-year students on an ambulatory medicine rotation. Our students universally viewed this activity as a high-quality presentation applicable to their careers. They strongly agreed that the cases facilitated a deeper understanding of the nuances of cancer screening. Discussion This TBL encourages learners to critically appraise cancer screening guidelines and apply them to real-life examples. It is applicable for learners who understand the complexities of patient care but still suffer from a guidelines-are-rules mentality.